Remembering or Forgetting Jerusalem? The Cultural Trauma of Exile - LUKÁCS, Ottilia (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
Using the Babylonian siege and exile as a case study, the paper examines how collective trauma was transformed into cultural memory and became constitutive of communal identity. The paper asks what enables a destroyed city to remain “alive” and how Jerusalem came to function as the singular idealized city of ancient Judah. Engaging the memory theory of Jan Assmann and the concept of cultural trauma developed by Jeffrey C. Alexander, it analyses two distinct trauma management strategies reflected in biblical texts. Ezekiel interprets the destruction theologically, framing exile as divinely ordained punishment and thereby rendering the catastrophe meaningful within a framework of guilt and repentance. In contrast, an anonymous psalmist preserves an emotional and symbolic attachment to the ruined city through an oath of remembrance and loyalty. Both figures function as cultural carriers who integrate the trauma of exile into the community’s self-understanding. By sustaining Jerusalem as a central reference point in cultural memory, they ensure that the destroyed city endures as a marker of collective ethnic and religious identity.